Proteinuria as a Marker of Cochlear Microvascular Damage and Functional Hearing Deficit in Presbycusis: A Cross-Sectional Study (Journal of Rangpur Medical College, 2026)
Background: Presbycusis is the most prevalent sensory deficit in older adults, its metabolic subtype involves progressive strial microvascular degeneration. Proteinuria, a systemic marker of endothelial dysfunction, may reflect parallel cochlear microvascular damage. Objective: To investigate the association between proteinuria and cochlear dysfunction in elderly patients with presbycusis. Methods: In this cross-sectional study, 340 adults aged ≥60 years with clinically confirmed presbycusis were enrolled and classified by proteinuria status (urine albumin-creatinine ratio [ACR] ≥30 mg/g). The Hearing Handicap Inventory for the Elderly–Screening Version (HHIE-S) and the Absolute Bone Conduction (ABC) test were used to assess functional hearing deficit. Results: Of 340 participants, 112 (32.9%) had proteinuria. The proteinuria group showed significantly higher mean HHIE-S scores (20.4±8.6 vs. 8.2±6.4; p